Blast-induced ground vibrations: a dynamic analysis by FEM (Research, Society and Development, 2022)
The peak particle velocities (PPV) are fundamental for understanding and managing the levels of blast-induced ground vibrations and their effects on adjacent structures. Given that numerical analysis of seismic vibrations has been demonstrated to be a method that can significantly contribute to predicting PPV, this study adopts a numerical approach using the finite element method (FEM) to assess blasting-induced ground vibration in rock masses. A dynamic module of the stress-strain analysis based on the FEM displacement formulation is developed in ANLOG software to estimate the variations of displacement, velocity, strain, and stress induced by blasting. The dynamic modulus implemented is verified using two verification examples. After, ANLOG is used in an application example to estimate seismic vibrations induced by blasting and to define the attenuation law for a limestone quarry near an urbanized area in Spain. The effect of Rayleigh damping coefficients (α and β) on the PPV levels estimated by ANLOG was investigated, and the most appropriate numerical attenuation law is then obtained. The numerical analysis presents satisfactory results for elastic-wave propagation induced by blasting and the peak particle velocity values obtained shows good agreement with field and the numerical results available in the specialized literature. The results indicate that ANLOG can perform personalized analysis of rock mass under blast-induced dynamic stress taking into consideration the geological and geomechanical characteristics particular to each medium as well as the blast parameters.